2003
DOI: 10.1142/s0217751x03016501
|View full text |Cite
|
Sign up to set email alerts
|

Finite Order BFFT Method

Abstract: We have proposed a method in the context of BFFT approach that leads to truncation of the infinite series regarded to constraints in the extended phase space, as well as other physical quantities (such as Hamiltonian). This has been done for cases where the matrix of Poisson brackets among the constraints is symplectic or constant. The method is applied to Proca model, single self dual chiral bosons and chiral Schwinger models as examples. *

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…As it has been stated before [23,24], there are more than one solution for equation (12). Thus, for a given second class system, there are so many corresponding first class systems which divert to it after gauge fixing.…”
Section: Bft Methodsmentioning
confidence: 88%
“…As it has been stated before [23,24], there are more than one solution for equation (12). Thus, for a given second class system, there are so many corresponding first class systems which divert to it after gauge fixing.…”
Section: Bft Methodsmentioning
confidence: 88%
“…In this way one can convert second class constraints to first class ones and then apply the well-known quantization method of gauge theories [4,5]. In our previous paper [6] we showed that if one chooses arbitrary parameters of the BFT method suitably then the power series of auxiliary fields for the embedded constraints and Hamiltonian could be truncated in some cases. In this Letter we want to preserve the chain structure of a second class system (except for the last element of the chain) during the BFT embedding.…”
mentioning
confidence: 99%
“…(14)-(16), respectively. We remind that [6], the aim is to choose a suitable solution for χ αβ in Eq. (17) such that the series for τ α andH truncates after a few steps.…”
mentioning
confidence: 99%
See 2 more Smart Citations